The impact of parental migration on the psychological wellbeing of abolescents from Mkoba 3 High School and Budiriro B College in Mkoba aged between 13 and 16 years. - Muuya, Agnes (Midlands State University, 2017)
The years 2000 to 2009 saw a lot of Zimbabweans from all walks of life experience a period of economic hardships. Many Zimbabwean parents out-migrated into neighboring countries and overseas in search of greener pastures, leaving their adolescent-children behind in their home country. The study sought to explore the impact of parental migration on the psychological well-being of adolescents at Mkoba 3 High School and Budiriro B College aged between thirteen and sixteen years with one or both parents working outside Zimbabwe. The study also sought to explore on how left-behind adolescents at Mkoba 3 High School and Budiriro B College aged between 13and 16 years view parental absence due to migration and how they cope with their situation. The research was prompted by the realization that a lot of parents in Mkoba are out-migrating leaving adolescents either on their own or with caregivers so the researcher saw the need to research on this topic. The study assumed that parental migration impacts negatively on the psychological well-being of adolescents. Qualitative methodologies were used. An exploratory design enabled the researcher to explore the experiences of the adolescents. Purposive sampling was used to come out with the twenty adolescents who participated in the study and the adolescents were chosen on the basis that they had one or both parents working outside Zimbabwe. In-depth interviews were used to allow the participants to share their own stories in their own words. The data that was gathered from the interviews was analyzed using thematic analysis. Thematic areas were extracted into which the data was categorized and analysed. The study confirmed findings by other scholars in their countries and revealed that parental absence due to migration has a negative impact on the psychological wellbeing of adolescents. Adolescents’ perceptions on parental absence and coping styles were also identified. Recommendations were made to schools, parents, caregivers, policy makers and for further study.